2011
DOI: 10.1002/jcu.20860
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic diagnosis of pulmonary embolism with cardiac arrest without major dilation of the right ventricle or direct sign of lower limb venous thrombosis

Abstract: Bedside focused echocardiography diagnosis of massive pulmonary embolism during cardiac arrest is mainly based on the detection of a dilated right ventricle, while the lack of compressibility of a deep vein of the lower limbs confirms diagnosis in doubtful cases. We describe a case of unusual sonographic signs in a young woman with cardiac arrest due to massive pulmonary embolism showing spontaneous blood echogenicity in the inferior vena cava ("sludge sign") and nonmodulated ("flat") Doppler waveform in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…All the intermediate conditions were considered not diagnostic. A third condition interpreted as sign of acute overload was visualization of spontaneous echo contrast (sludge) or solid echogenic thrombi [29].…”
Section: Ultrasonography Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…All the intermediate conditions were considered not diagnostic. A third condition interpreted as sign of acute overload was visualization of spontaneous echo contrast (sludge) or solid echogenic thrombi [29].…”
Section: Ultrasonography Techniquementioning
confidence: 99%
“…Absence of collapsibility was considered diagnostic for intra-luminal thrombosis [32]. In case of negative examination but strong suspicion for thrombosis, the bilateral venous waveform was analyzed by color-doppler to check for asymmetry indicating proximal obstruction [29].…”
Section: Ultrasonography Techniquementioning
confidence: 99%
“…Of course, these signs are a product of a large flow-obstructing PE altering hemodynamic physiology in the presence of spontaneous circulation, a factor that is not present at CA. However, several case reports and observational studies have reported that, even during CA, PE can still be identified using the same signs of disproportionate RV size and direct embolism visualization in the pulmonary artery, right atrium, or IVC as a homogenously echogenic structure independent of underlying anatomy (suggestive of thrombus presence [21][22][23][24][25]. Such findings may lead to change in management including use of thrombolysis, an intervention that could largely benefit mortality in these patients [26,27].…”
Section: Pulmonary Embolus With Acute Cor Pulmonalementioning
confidence: 99%
“…However, depending on the setting, the vessel observed and the patient condition, the rouleaux (or sludge sign) should sometimes induce to extend the observation to the possibility of proximal obstruction. The sludge sign in the inferior vena cava during cardiac arrest with electrical activity and hyperkinetic left cardiac chambers may be a sign of acute right overload [45]. The same sign in the femoral vein, corroborated by asymmetric femoral veins waveforms at color Doppler analysis, may be a sign of isolated iliac thrombus [45].…”
Section: Introductionmentioning
confidence: 99%
“…The sludge sign in the inferior vena cava during cardiac arrest with electrical activity and hyperkinetic left cardiac chambers may be a sign of acute right overload [45]. The same sign in the femoral vein, corroborated by asymmetric femoral veins waveforms at color Doppler analysis, may be a sign of isolated iliac thrombus [45]. …”
Section: Introductionmentioning
confidence: 99%